Factors Influencing Customers’ Purchase Intention towards Local Clothing Brands in Bangladesh - Mehtaj, Mouri (American Journal of Trade and Policy, 2017)
This study is an attempt to determine the factors influencing customers to purchase local clothing brands. Data was collected through self-administered questionnaire. Total 350 respondents from specific geographical areas (Dhaka, Chittagong and Sylhet) have been selected to conduct the study. Cross tabulation was used for the analysis of collected data under the support of IBM SPSS 16. The study addressed some important features regarding choice of clothes. The findings indicate that quality is the first priority among all the factors for preferring local brands. Promotional activities have more influence on male customers instead of female customers. Other factors like variation, reasonable price and scope for change are less important factors for the adult buyers.